Development prospect of nutmeg (Myristica fragrans Houtt) in the community forest - Eva Fauziyah; Devy Priambodo Kuswantoro; Sanudin Sanudin (Jurnal Ilmu Kehutanan)
The private forest is largely managed with agroforestry pattern. Nutmeg (Myristica fragrans) is a plant that has been developed in the private forest. This study aimed to determine the prospect of nutmeg in the private forest. This research was conducted in the Kemawi village, Somagede Subdistrict of Banyumas District, Central Java Province in June to July 2012. Data were collected through secondary data study, open and in-depth interviews. Twenty farmers who planted nutmeg were selected with purposive sampling technique. The obtained data were processed and analyzed descriptively. The results showed that nutmeg had a good prospect as one of the plantation species for private forest development in Kemawi village because of these several factors: 1) Kemawi land was biophysically suitable for nutmeg plantation, 2) socially, many farmers had been planting nutmeg in their land, 3) economically, nutmeg had a good and stable price that can provide additional income, 4) marketing of both fruit and seed of nutmeg were very easy, and 5) there were good attentions from the government to the nutmeg development program from production to post-harvesting process.